IMPACT OF SOCIAL MEDIA MARKETING AND ELECTRONIC WORD OF MOUTH (E-WOM) ON PURCHASE INTENTION - Winarno, Kania Oktaviana; Indrawati, Indrawati (Universitas Brawijaya, Indonesia, 2022)
The present quantitative research is intended to conduct an investigation into the effect of social media marketing and electronic word of mouth (E-WOM), especially on Instagram, on the purchase intention of Sunday Bowl Cereal Club products. As for the sampling strategy, the non-probability purposive sampling method was employed in this research. Samples were drawn from up to 300 respondents. To analyze the data, this research employed the Structural Equation Modeling (SEM) models that are processed using SmartPLS 3.2.9. The results show that social media marketing has a positive and significant relationship to E-WOM. Age and gender moderate the relationship between social media marketing and E-WOM. Social media marketing has a positive and significant relationship on purchase intention. Age and gender do not moderate the relationship between social media marketing and purchase intention. E-WOM has a positive and significant relationship on purchase intention. Age moderate the relationship between E-WOM and purchase intention. Gender do not moderate the relationship between E-WOM and purchase intention. Social media marketing has a positive and significant relationship on purchase intention through E-WOM. Age moderate the relationship between Social media marketing and purchase intention through E-WOM. Gender do not moderate the relationship between social media marketing and purchase intention through E-WOM. Sunday Bowl Cereal Club needs to pay attention to the framework in the customer life cycle: Plan-Reach-Act to increase their social media marketing. Then Sunday Bowl Cereal Club needs to improve its marketing mix through E-WOM in encouraging purchase intention from potential customers.